The protective effect of dietary supplementation of Salmonella-specific bacteriophages in post-weaning piglets challenged with Salmonella typhimurium (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The efficacy of Salmonella typhimurium-specific bacteriophage STP-1 on S. typhimurium infection in weaning piglets was evaluated in this study.  Material and Methods: Twenty-eight weaning piglets were randomly allocated to four groups (Group A: non-challenged/basal; Group B: non-challenged/+phage; Group C: challenged/basal; Group D: challenged/+phage) according to S. typhimurium infection or bacteriophage administration. The total experimental period (14 days) was subdivided in to non-challenged periods (phase I; day 1–7) and challenged periods (phase II; day 7–14) based on the challenging date (day 7). Each group was fed with basal feed or feed supplemented with bacteriophage STP-1 [1.0 × 109 plaque-forming unit (PFU)/kg] during the whole period (day 1–14). Body weights (BW) were measured to evaluate growth performance. Clinical symptoms (rectal temperatures and fecal consistency) induced by S. typhimurium were regularly checked. Bacteria colonization levels in feces and intestinal tissue samples were measured using real-time polymerase chain reaction (PCR). After necropsy, small intestine samples (jejunum) were collected. Villus height and crypt depth (CD) were measured through histological examination with H&E staining.  Results: The supplementation of bacteriophage significantly reduced bacterial colonization and intestine damage in the piglets infected with S. typhimurium. In the antigen concentrations of the feces and jejunum, Group C showed 5.8 ± 0.6, 5.7 ± 0.6, and 1.2 ± 2.0 log colony-forming unit (CFU)/ml on 1, 3, and 7 days post-inoculation (DPI) and 2.8 ± 1.3 log CFU/ml, whereas Group D showed 3.5 ± 1.7, 2.2 ± 2.1, and 0.3 ± 0.9 log CFU/ml on 1, 3, and 7 DPI and 5.1 ± 0.9 log CFU/ml. In the villous height, Groups C and D showed 266.3 ± 24.1 and 324.6 ± 18.0 μm, respectively. In the goblet cell density of villi and crypts, Group C showed 10.0 ± 1.8 and 16.0 ± 3.7, while Group D showed 15.0 ± 4.8 and 21.1 ± 5.4. Also, the supplementation of bacteriophage significantly improved the growth performance in the infected piglets. The average daily gains of Groups C and D were 91 ± 24 and 143 ± 23, respectively, during the period after inoculation with S. typhimurium.  Conclusion: The dietary supplementation of the phage was effective for alleviating S. typhimurium infection in post-weaning piglets.J. Adv. Vet. Anim. Res., 8(2): 440-447, June 2021http://doi.org/10.5455/javar.2021.h532